Pengembangan Rumah Software Sebagai Upaya Melatih Jiwa Kewirausahaan Mahasiswa Teknik Informatika - Selvia Ferdiana Kusuma; Ratna Widyastuti (Politeknik Negeri Banjarmasin, 2019)
Students are one of the agents of change. The development of a region will depend on the younger generation activities. Therefore, the young generation development needs to be considered. Today the information technology is developing very rapidly, but the momentum cannot be utilized by Informatics Engineering students. Even though they can be connected and collaborate with each other, it is possible to come up with new products that can help the development of Indonesia, especially in the field of Information Technology. The majority of them do not know how to start doing business in the Information Technology field. In this community service program, the proponent proposes an idea to solve the problem by developing a student software home website to display products that have been created and are ready for sale. This website is used as a promotional media which able to introduce and promote products produced by Informatics Engineering students. The existence of this home software website will not only bring benefits to students but also can bring benefits to the community in general. Citizens who want to find out about the desired software creation services do not need to feel difficult again for looking information because all information related to the desired software products is provided on this website. This home software website creation program is carried out in 5 stages: preparation, requirements analysis, website creation, implementation, and report generation. Now the student software home website become an information media that can provide information related to service products provided by Informatics Engineering students.